2016
DOI: 10.1590/0001-3765201620140434
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of mercury, cadmium, zinc, chromium, and lead in muscle, liver, and spleen tissues of a large commercially valuable catfish species from Brazil

Abstract: The increasing amounts of heavy metals entering aquatic environments can result in high accumulation levels of these contaminants in fi sh and their consumers, which pose a serious risk to ecosystems and human health. We investigated the concentrations of mercury (Hg), cadmium (Cd), zinc (Zn), chromium (Cr), and lead (Pb) in muscle, liver, and spleen tissues of Pseudoplatystoma corruscans specimens collected from two sites on the Paraopeba River, Brazil. The level of heavy metals concentrations in the tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 36 publications
1
35
1
6
Order By: Relevance
“…Autophagy is one of the crucial cellular mechanisms for organism, in which mTOR negatively regulates the induction of autophagy [11]. Corsetti et al (2016) reported that spleen is one of the target organs of Pb toxicity; excessive exposure to Pb may induce autophagy in the spleen [12]; in fishes, spleen exhibits a high content of Pb and histopathological alterations when treated by Pb [13]. Additionally, the evidence convinced that mitochondrial fission could promote mitochondrial autophagy in mouse embryonic fibroblasts, human fibroblasts, and cardiac cells [1416]; in adult cardiomyocytes, Drp1, a GTPase, regulates mitochondrial fission, and mediates autophagy [17]; the overexpression of the OPA1 decreases mitochondrial autophagy in mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is one of the crucial cellular mechanisms for organism, in which mTOR negatively regulates the induction of autophagy [11]. Corsetti et al (2016) reported that spleen is one of the target organs of Pb toxicity; excessive exposure to Pb may induce autophagy in the spleen [12]; in fishes, spleen exhibits a high content of Pb and histopathological alterations when treated by Pb [13]. Additionally, the evidence convinced that mitochondrial fission could promote mitochondrial autophagy in mouse embryonic fibroblasts, human fibroblasts, and cardiac cells [1416]; in adult cardiomyocytes, Drp1, a GTPase, regulates mitochondrial fission, and mediates autophagy [17]; the overexpression of the OPA1 decreases mitochondrial autophagy in mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation rate of heavy metals in the body of an organism depends on its concentration in waters, temperature, species and physiological condition (Mu'nisa and Nurham, 2010) and feeding habits of the animal (Sarong et al, 2013). However, the highest metal accumulation is usually in liver and kidney (Arantes et al, 2016). Generally the content of heavy metals in water and muscles is usually lower than the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…However, heavy metals determination in human kidney, liver and lungs are very scarce as compared to that of animal's specimen. For example, there were reports on heavy metals in: the livers and kidneys of slaughtered cattle, sheep and goats [16,17]; liver, kidney and meat of beef (cow), mutton (sheep), caprine (goat) and chicken [18]; blood and various organs (lung, liver, kidney and cerebral cortex) of rats [19]; muscle, liver, and spleen tissues of a large commercially valuable catfish species from Brazil [20]; and a one-time high dose oral administration of heavy metals mixture (HMMs) induced systemic toxicity in rats [21] have also been reported. However, few cases of studies of heavy metals in human kidney [22]; 10 autopsied human organs (liver, kidney, cerebrum, heart, spleen, lung, bone, blood, hair and nail) of Koreans [23] and the liver tissues of autopsy cases in Ankara, Turkey [24] have been investigated.…”
Section: Introductionmentioning
confidence: 99%